A revision of the genera Galeolaria and Pyrgopolon (Polychaeta: Serpulidae), with discussions on opercular insertion as a character in their taxonomy and relationships, and their zoogeography - Pillai, T. Gottfried (Zootaxa, 2009)
While earlier works have shown that the operculum is inserted in the position of the first or second branchial radiole in serpulimorph taxa, the present paper shows that it is inserted independently of the branchial radioles of both sides in the genera Galeolaria and Pyrgopolon. Although both genera possess several characters in common with the group consisting of Pomatoleios, Pomatoceros and Spirobranchus, a cladistic analysis revealed that they form two distinct clades, as sister groups to each other. Extant species of Pyrgopolon occur mainly in the Caribbean region, and of Galeolaria in eastern Australia and New Zealand. However, there is palaeontological evidence indicating that fossil species of Pyrgopolon had a wider geographical distribution, having existed in Europe during geological times.